Fecal short chain fatty acids modify therapeutic effects of sleeve gastrectomy - Shen, Chongrong; Chen, Yanru; Wang, Qiaoling; Sun, Yingkai; Lin, Huibin; Ni, Mengshan; Chen, Yufei; Zhang, Ling; Jin, Jiabin; Ying, Xiayang; Zou, Yuyao; Wang, Xiaolin; et al. (Frontiers in Endocrinology, 2023)
Aims: We aimed to investigate changes of fecal short chain fatty acids (SCFAs) and their association with metabolic benefits after sleeve gastrectomy (SG). Specifically, whether pre-surgery SCFAs modify surgical therapeutic effects was determined. Methods: 62 participants with measurements of fecal SCFAs and metabolic indices before and 1, 3, 6 months after SG were included. Changes of fecal SCFAs and their association with post-surgery metabolic benefits was calculated. Then, participants were stratified by medians of pre-surgery fecal SCFAs and modification effects of pre-surgery fecal SCFAs on surgical therapeutic effects were investigated, through calculating interaction of group by surgery. Results: Fecal SCFAs were markedly changed by SG. Changes of propionate and acetate were positively correlated with serum triglycerides and total cholesterol, respectively. Notably, high pre-surgery fecal hexanoate group showed a better effect of SG treatment on lowering body weight (P=0.01), BMI (P=0.041) and serum triglycerides (P=0.031), and low pre-surgery fecal butyrate had a better effect of SG on lowering ALT (P=0.003) and AST (P=0.019). Conclusions: Fecal SCFAs were changed and correlated with lipid profiles improvement after SG. Pre-surgery fecal hexanoate and butyrate were potential modifiers impacting metabolic benefits of SG.